The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1104/pp.87.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mRNAs that Accumulate in Response to Low Temperature Identifies a Thiol Protease Gene in Tomato

Abstract: We have studied the induction of gene expression at low temperature by cloning mRNAs that accumulate when unripe tomato (Lycopersicon esculentum) fruit are incubated at 4°C. Two DNA sequence analysis indicates that the C14 mRNA encodes a polypeptide with a region that is homologous to the plant thiol proteases actinidin and papain and to the animal thiol protease cathepsin H. We conclude from these experiments that low temperature selectively induces the expression of specific genes and that one such gene en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
100
1
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 31 publications
0
100
1
1
Order By: Relevance
“…A low-temperature-inducible thiol protease cDNA has been cloned from tomato fruit (Schaffer and Fischer, 1988). The tomato cDNA shares regions of homology with other plant proteases and with the animal protease cathepsin H. The bromegrass pBGA85 clone is not only ABA responsive, but is also cold responsive, like the tomato thiol protease gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low-temperature-inducible thiol protease cDNA has been cloned from tomato fruit (Schaffer and Fischer, 1988). The tomato cDNA shares regions of homology with other plant proteases and with the animal protease cathepsin H. The bromegrass pBGA85 clone is not only ABA responsive, but is also cold responsive, like the tomato thiol protease gene.…”
Section: Discussionmentioning
confidence: 99%
“…The tomato cDNA shares regions of homology with other plant proteases and with the animal protease cathepsin H. The bromegrass pBGA85 clone is not only ABA responsive, but is also cold responsive, like the tomato thiol protease gene. Schaffer and Fischer (1988) have suggested that low temperatures may denature certain polypeptides, thus creating a requirement for proteases to degrade the denatured ' polypeptides. Cold-and ABA-induced protease expression may, therefore, play a more important role in supporting cellular metabolism during low-temperature growth than in developing hardiness.…”
Section: Discussionmentioning
confidence: 99%
“…A number of putative thiol proteases have been identified from the sequence of cDNAs isolated from various plants. In tomato (Lycopersicon esculentum) fruit, a putative enzyme, C14, accumulates in response to low temperatures (31). A different thiol protease-encoding mRNA, COT44, accumulates in the vascular tissue and the epidermis of Brassica napus seedlings (9).…”
mentioning
confidence: 99%
“…We previously reported the cloning and analysis of cDNAs representing mRNAs that accumulate following exposure of tomato fruit to 4°C (30). The concentration of two of these mRNAs increased relatively rapidly in response to low temperature and decreased upon removal ofthe stress.…”
mentioning
confidence: 99%
“…Exposure to low nonfreezing temperature causes accumulation of specific mRNAs in tomato fruit (30) and alfalfa (26), and elicits alterations in protein profiles from in vitro translated RNA of barley (4), Arabidopsis (13,18), rapeseed (25), and spinach (15).…”
mentioning
confidence: 99%